2018
DOI: 10.1039/c8ta02061b
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-driven water-splitting using two-dimensional carbon based semiconductors

Abstract: 2D carbon semiconductors and composites are highly promising photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
114
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(114 citation statements)
references
References 446 publications
0
114
0
Order By: Relevance
“…The photocatalytic performance increases with the decrease of thickness of 2D BiOCl x Br 1‐x nanosheets. According to the diffusion equation: truenormalt=normald2/normalk2normalD …”
Section: Resultsmentioning
confidence: 99%
“…The photocatalytic performance increases with the decrease of thickness of 2D BiOCl x Br 1‐x nanosheets. According to the diffusion equation: truenormalt=normald2/normalk2normalD …”
Section: Resultsmentioning
confidence: 99%
“…The Mott-Schottky (M-S) plots were performed to further analyze the electron transfer characteristic of the samples ( Figure 8E and F). The VB potential of rGO is confirmed as 2.13 eV by XPS VBs analysis, and it is well known that the HOMO of rGO is very close to its LUMO, 84,85 so that its π→π* transition can easily be induced by visible-light. Hereby, the positive slope of rGO and negative slope of AgBr make them into the typical electron-rich donor and electron-deficient receptor.…”
Section: Catalytic Mechanismmentioning
confidence: 81%
“…82,83 Based on aforementioned research, the VLD catalytic mechanism of rGAA-α catalyst was confirmed to be the model as Figure 9. The VB potential of rGO is confirmed as 2.13 eV by XPS VBs analysis, and it is well known that the HOMO of rGO is very close to its LUMO, 84,85 so that its π→π* transition can easily be induced by visible-light. For the closer VB potential (1.64 eV) of AgBr with LUMO orbital of rGO, the typical electron transfer model of Z-scheme heterointerface can be formed between AgBr and rGO, which is also verified by M-S analysis.…”
Section: Catalytic Mechanismmentioning
confidence: 81%
See 2 more Smart Citations